Diseño de un biosensor de tipo flujo lateral para la detección de Helicobacter pylori y su factor de virulencia cagA (2017)
Helicobacter pylori (H. pylori) is a Gram-negative bacterium that colonizes the surface of gastric mucosa due to its unique characteristics. It is distributed worldwide and has a determining role in the development of gastritis, peptic ulcers and other pathologies. Evidence suggests that chronic infection with H. pylori increases the risk of gastric cancer and hence has been classified as a type I carcinogen by the WHO. The infection is highly variable and is influenced by genetic factors of the bacterium, the host and the environment for which we aim to detect the gene that codifies for the virulence factor cagA, associated with more severe clinical results. Despite its clinical relevance, the diagnostic methods are not fully accepted due to sensitivity and specificity. Therefore, the design of a lateral flow assay for the detection of H. pylori and cagA gene is proposed in this study. As results, a functional sensor with a minimum and maximum detection levels of 2.5 and 800 ng/æL respectively was obtained with an estimated reading time of 15 minutes. These results represent an innovative alternative for the detection of H. pylori and its cagA gene that could solve the current diagnostic problems by providing a rapid and sensitive response for the detection and treatment of this microorganism.--Tomado del Formato de Documento de Grado.